Trend 2002 - 2007. Statistics Canada. CANSIM: Retail and Wholesale - Retail Sales by Type of Store | Country: Canada | Province: Newfoundland and Labrador | Table: Annual retail store survey, financial estimates by store type and trade group based on the North American Industry Classification System (NAICS) | Variable: Closing inventory, Chain stores, Clothing stores | Units: , 2002-2007. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-177. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Retail and Wholesale - Retail Sales by Type of Store | Country: Canada | Province: Newfoundland and Labrador | Table: Annual retail store survey, financial estimates by store type and trade group based on the North American Industry Classification System (NAICS) | Variable: Closing inventory, Chain stores, Clothing stores | Units: , 2002-2007. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-177. Dataset: Provides statistics on sales estimates of all goods purchased for resale, net of returns and discounts, by type of retail outlet, in Canada. The retail industry is primarily engaged in selling consumer goods and related services to the general public. Based on the North American Industry Classification System (NAICS) definition of retail trade, major trade groups (retail outlet type) are covered using special aggregations of the 2002 NAICS industries. Annual estimates of revenues, expenses, and inventories are available for all types of retailing, with additional information provided on retail chains. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Industry, Business, and Commerce Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Retail Sales, Consumer Products, Retail Stores, Retail Trade